Religious publications and youth in the context ofreligious education: the case of high school studentsin İstanbul - GÜRER, BANU (My University, 2023)
One of the most important features of today's world is that change takes place rapidly. One of the most important areas where change takes place is information resources. With the development of technology, information sources have diversified, and the diversified information sources have increased both the opportunity to access information and the speed of information dissemination. It is possible to say that these developments have affected the relationship of with the book, which is one of the ancient sources of information, and thus also the reading habits. In particular, the increase in the speed and opportunity of accessing the Internet has brought with it the tendency to apply to online resources rather than published books in order to meet the need for any information or news. It can be stated that this tendency affects not only the rate of reading books, but also the reason and form of it. With the increase in digitalization, the findings that there is a transition from deep/intensive reading to widespread and superficial/technical reading in reading behaviors are important in terms of drawing attention to this change. These changes also affect the status of religious publications as a source of religious education, bringing the target audience's interest in this field to the agenda as a problem area. Youth and their habits of religious publications reading, as one of the most important segments where the mentioned changes affect reading habits, and the place of religious publications among these habits constitute an important dimension in understanding the relationship between youth and religion in context of religious education. As a matter of the fact, the problems in the number and quality of studies for young people in the field of religious publications attract attention as a current area of discussion. Based on the aforementioned issues, our research aims to understand the reading habits of young people, their perspectives on religious publication and the place of religious publication in their reading habits, together with its reasons, in a comparative way for Religious High School and High School for Science students in İstanbul, Turkey. The data of the study, which was carried out using the interview technique structured with a phenomenological design, were obtained from a total of 20 participants, 10 from each group. The data will be analyzed under four main themes in context of religious education: culture of reading, culture of reading religious publications, views and perceptions of religious publications, and problems and expectations, and it will be aimed to make suggestions for studies in the field of religious publishing from perspective of religious education.
Keywords: Religious education; youth; religion; religious publication; reading culture